Fenomena “Digital Fatigue” Pada Mahasiswa Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang - Febreza, Fadlan; Junaidi, Junaidi (Naradidik: Journal of Education and Pedagogy, 2022)
This research started from changes that occurred in the world of education during the COVID-19 pandemic made the lecture system change from online to offline. As a result of these changes, students are physically and psychologically exhausted, which causes the phenomenon of Digital Fatigue. The purpose of this study was to analyze the form of Digital Fatigue and its impact on students of the Department of Sociology, Faculty of Social Sciences (FIS) Universitas Negeri Padang (UNP). This study uses a qualitative approach. The research informant selection technique used purposive sampling technique with a total of 19 people. Data collection techniques are observation techniques, in-depth interviews, and documentation studies. Data analysis was carried out using the Miles and Huberman interactive model. The results of this study indicate that there are several forms and impacts of the digital fatigue phenomenon on students majoring in sociology at the Padang State University which are divided into physical digital fatigue, psychological digital fatigue. and the impact of digital fatigue on student studies, finances and social interactions. Physical digital fatigue consists of disturbances in the eyes, head and body. While digital psychological fatigue consists of disturbances in mood, decreased interest and motivation and FOMO. The impact of digital fatigue on student studies causes a decrease in learning outcomes, as well as neglected assignments, on finances causing the economy to decline due to frequent buying of internet quota, as well as on social interactions affecting how to interact and communicate.